Effectiveness of Continuum of Care-Linking Pre-Pregnancy Care and Pregnancy Care to Improve Neonatal and Perinatal Mortality: A Systematic Review and Meta-Analysis. - Kimiyo Kikuchi; Sumiyo Okawa; Collins O F Zamawe; Akira Shibanuma; Keiko Nanishi; Azusa Iwamoto; Yu Mon Saw; Masamine Jimba (PLoS ONE)
Review registration PROSPERO International prospective register of systematic reviews (CRD42015023424).